Microbial Transformations of Nitrogen, Sulfur, and Iron Dictate Vegetation Composition in Wetlands: A Review - Lamers, Leon P.; Van Diggelen, Josepha M.; Op Den Camp, Huub J.; Visser, Eric J.; Lucassen, Esther C.; Vile, Melanie A.; Jetten, Mike S.; Smolders, Alfons J.; Roelofs, Jan G. (Frontiers in Microbiology, 2012)
The majority of studies on rhizospheric interactions between microbial communities and vegetation focus on pathogens, mycorrhizal symbiosis, and/or carbon transformations. Although the biogeochemical transformations of nitrogen (N), sulfur (S) and iron (Fe) have profound effects on plants, these effects have received far less attention. Firstly, all three elements are plant nutrients, and microbial activity significantly changes their mobility and availability. Secondly, microbial oxidation with oxygen supplied by radial oxygen loss (ROL) from roots in wetlands causes acidification, while reduction using alternative electron acceptors leads to generation of alkalinity, affecting pH in the rhizosphere and hence plant composition. Thirdly, reduced species of all three elements may become phytotoxic. In addition, Fe cycling is tightly linked to that of S and phosphorus (P). As water level fluctuations are very common in wetlands, rapid changes in the availability of oxygen and alternative terminal electron acceptors will result in strong changes in the prevalent microbial redox reactions, with significant effects on plant growth. Depending on geological and hydrological settings, these interacting microbial transformations change the conditions and resource availability for plants, which are strong drivers of vegetation development and composition by changing relative competitive strengths. Conversely, microbial composition is strongly driven by vegetation composition. Therefore, the combination of micro- and macroecological knowledge is essential to understand the biogeochemical and biological key factors driving heterogeneity and total (i.e., micro-macro) community composition at different spatial and temporal scales. As N and S inputs have drastically increased due to anthropogenic forcing and Fe inputs have decreased at a global scale, this combined approach has become even more urgent.